Evaluation of the role of marbling texture on beef palatability - Vierck, Kelly (Kansas State University, 2017)
The objective of this research was to evaluate the role of marbling texture on beef palatability, muscle histology, and collagen characteristics of beef strip loin steaks. Beef strip loins (n = 117) were selected from three quality grade treatments [Top Choice (Modest[superscript 00] – Moderate[superscript 100] marbling), Low Choice (Small[superscript 0] – Small[superscript 100] marbling), and Select (Slight[superscript 0] – Slight[superscript 100] marbling)] to equally represent three different marbling texture groups: fine, medium and coarse, via visual appraisal with the USDA marbling texture standards. Consumers (n = 104) rated all marbling texture groups similar (P > 0.05) for tenderness, juiciness, flavor, and overall liking, as well as rated a similar (P > 0.05) percentage of samples from each marbling texture group acceptable for each palatability trait. Moreover, consumers indicated no preference (P > 0.05) among marbling texture groups for visual desirability or likelihood to purchase. There were no differences (P > 0.05) among marbling texture treatments for Warner-Bratzler shear force, slice shear force, and pressed juice percentage. However, trained sensory panelists rated coarse marbled steaks higher (P < 0.05) than fine or medium marbled steaks for both beef flavor intensity and sustained juiciness as well as higher (P < 0.05) for initial juiciness than medium textured steaks. This minimal impact on palatability was further supported through evaluation of muscle histology and collagen traits. Marbling texture did not affect collagen characteristics, as coarse marbled steaks were similar (P > 0.05) to both fine and medium marbled steaks for soluble collagen, insoluble collagen, and total collagen content. Furthermore, all marbling texture groups (fine, medium, and coarse) performed similarly (P > 0.05) during the peak thermal transition phase of the perimysial fraction of collagen. However, marbling texture impacted (P < 0.05) adipocyte cross-sectional area, where coarse steaks had larger adipocytes in comparison to fine marbled steaks, but medium marbled steaks were similar (P > 0.05) to both coarse and fine marbled steaks. Similarly, quality grade affected adipocyte size, as Top Choice and Low Choice possessed larger (P < 0.05) adipocytes than Select steaks. However, marbling texture did not impact (P > 0.05) perimysial thickness. Additionally, marbling texture did not affect the percentage of myosin heavy chain (MHC) Type I fibers within each steak. However, medium marbled steaks possessed a greater (P < 0.05) percentage of MHC Type 2A fibers than both fine and coarse marbled steaks. The opposite trend was displayed in the percentage of MHC Type IIX fibers, as fine and coarse marbled steaks possessed more (P < 0.05) MHC Type IIX fibers in comparison to medium marbled steaks. There were no differences (P > 0.05) among quality grades for fiber type or marbling texture and quality grade for fiber cross-sectional area. Results from this study indicate marbling texture has minimal impact on eating quality and muscle histology; therefore coarse marbled carcasses should not be excluded from current and future branded beef programs.
Keywords: Beef; Consumer; Marbling texture; Palatability; Quality grade; Sensory